2007
DOI: 10.1172/jci25483
|View full text |Cite
|
Sign up to set email alerts
|

Extrapancreatic incretin receptors modulate glucose homeostasis, body weight, and energy expenditure

Abstract: The incretin hormones glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) control glucose homeostasis through well-defined actions on the islet β cell via stimulation of insulin secretion and preservation and expansion of β cell mass. We examined the importance of endogenous incretin receptors for control of glucose homeostasis through analysis of Glp1r -/-, Gipr -/-, and double incretin receptor knockout (DIRKO) mice fed a high-fat (HF) diet. DIRKO mice failed to upregulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
219
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(253 citation statements)
references
References 37 publications
32
219
2
Order By: Relevance
“…Circulating adipokines were not appreciably affected by (Pro 3 )GIP, with only a small possibly beneficial decrease in resistin observed. This does not indicate a significant GIPergic adipokine generation in ob/ob mice and questions their recently postulated role in alleviating insulin sensitivity in GIP receptor knockout mice [43]. The abnormal lipid profile also persisted in ob/ob mice treated with (Pro 3 )GIP, but there were significant improvements in triacylglycerol and LDL-cholesterol.…”
Section: Discussionmentioning
confidence: 53%
“…Circulating adipokines were not appreciably affected by (Pro 3 )GIP, with only a small possibly beneficial decrease in resistin observed. This does not indicate a significant GIPergic adipokine generation in ob/ob mice and questions their recently postulated role in alleviating insulin sensitivity in GIP receptor knockout mice [43]. The abnormal lipid profile also persisted in ob/ob mice treated with (Pro 3 )GIP, but there were significant improvements in triacylglycerol and LDL-cholesterol.…”
Section: Discussionmentioning
confidence: 53%
“…1 Differences in food intake induced by exendin-4 therapy may have made a contribution to these effects, but additional experiments are required to single out direct effects of peptide administration on brain function. The reason why bodyweight did not change with exendin-4 treatment may point to an effect of GLP-1 on physical activity and energy expenditure as observed in knockout mice, 11 however, further studies are necessary to confirm this. However, the object recognition test clearly showed that mice fed a high-fat diet exhibited notable impairments in cognitive performance as they failed to discriminate between the familiar and the novel object.…”
Section: Discussionmentioning
confidence: 97%
“…A DPP‐4 inhibitor is used for treating patients with type 2 diabetes. The main mechanism for its anti‐diabetic effect is to inhibit DPP‐4, a degradative enzyme of incretin hormones such as GLP‐1 and glucose‐dependent insulinotropic polypeptide 36. Incretin has been known to exert pleiotropic effects on the central nervous system, the liver, cardiovascular, lung, kidney, or skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%